Compensatory changes in female running mechanics during a simulated 10 km race - Fuhr, D. P.; Chiu, L. Z. F.; Kennedy, M. D. (Journal of Human Sport & Exercise, 2018)
During a 10 km run at race pace, changes in lower extremity mechanics have been reported in male runners however mechanical changes over 10 km in female runners is unknown. Thus we aimed to examine running mechanics in females during a simulated 10 km race on a treadmill. Nine female distance runners (age: 32.1±4.2 yrs; ht: 166.7 ± 7.4 cm; wt: 57.8 ± 7.0 kg; VO2max = 3.24 ± 0.50 L/min) completed graded exercise testing (Day 1); 10km time trial (Day 2); and simulated 10km treadmill run (DAY 3; 95 % of running velocity from Day 2 time-trial). Mechanical data sampled at 120Hz using a 6-camera optoelectronic motion capture system and effort (Rating of Perceived Exertion - RPE) were measured at 50, 1450, 2950, 4450, 5950, 7450, 8950 and 9950 metres. Maximum voluntary contraction of knee extensors was measured pre-post. Seven participants decreased MVC (1-21% decrease) and RPE increased from 12 (50m) to 19 (9950m). Step frequency decreased 3 steps/min (p<0.05) and step length increased 3cm. Max knee extension and max knee flexion increased from 50m to 9950m and hip height was lowered over the 10km time-trial. These results indicate that whole body fatigue influences RPE and is associated with mechanical changes to maintain pace in female runners. Specifically, the combination of knee extension and knee flexion increases likely reduces limb inertia as the runner fatigues minimizing decreases in step frequency and improving step length. These results are the first to illuminate the fatigue related intrinsic coping mechanisms of female runners at race pace.